P.054 Electroconvulsive therapy and epilepsy: a case report. (June 2019) - Kassiri, J; Ogilvie, R; Elliott, C; Sinclair, DB
Abstract : Background: Electroconvulsive therapy (ECT) involves the induction of a generalized seizure with an electrical current and has been used worldwide when treating medically refractory psychiatric illness. Here we describe a patient with no prior history or risk factors for epilepsy who developed temporal lobe epilepsy after chronic treatment of ECT. Methods: A 16-year-old right-handed boy with severe refractory depression received ECT treatment every 10 days for 8 months. Six months into his ECT treatment, the patient developed seizures and was admitted to a pediatric epilepsy monitoring unit. Results: Initial clinical events included lightheadedness, diaphoresis, and nausea with associated kaleidoscopic vision changes. Seizures progressed to confusion, fear and paranoia by the time the patient was admitted for monitoring. Long-term video EEG captured many focal seizures with impaired awareness, all originating from both temporal lobes. MRI was normal. ECT was terminated and the patient started on carbamazepine. He has been seizure free for the past 2 years on medication Conclusions: While rare, we present a case of a patient with no prior risk factors for epilepsy who developed temporal lobe epilepsy after chronic ECT treatment. Although ECT is an indispensable treatment for many medically refractory psychiatric illnesses, we suggest caution in young patient undergoing ECT.